x = 3 - 2x = 6, x = 5 - 3x + 6 = 21, x = 9 - 5x - 4 = 41, x = 2 - 6x + 5 = 17, x = 4 - 5x - 3 = 17, x = 2.5 - 2x = 5, x = 7 - 4x - 15 = 13, x = 6 - 6x - 9 = 27,
Algebra equations one step foundation
Share
Share
by Anonymous
KS3
KS4
Maths
Algebra
Like
Edit Content
Embed
More
Log in required
Theme
Fonts
Default
Primary
Handwriting
Modern
Geometric
Traditional
Log in required
Options
Leaderboard
Show more
Show less
This leaderboard is currently private. Click
Share
to make it public.
This leaderboard has been disabled by the resource owner.
This leaderboard is disabled as your options are different to the resource owner.
Revert Options
Switch template
Interactives
Show all
More formats will appear as you play the activity.
Restore auto-saved:
?